Substrate topography guides pore morphology evolution in nanoporous gold thin films. (1st January 2016) - Chapman, Christopher A.R.; Daggumati, Pallavi; Gott, Shannon C.; Rao, Masaru P.; Seker, Erkin
Graphical abstract: Abstract: This paper illustrates the effect of substrate topography on morphology evolution in nanoporous gold (np-Au) thin films. One micron-high silicon ridges with widths varying between 150 nm and 50 μm were fabricated and coated with 500 nm-thick np-Au films obtained by dealloying sputtered gold–silver alloy films. Analysis of scanning electron micrographs of the np-Au films following dealloying and thermal annealing revealed two distinct regimes where the ratio of film thickness to ridge width determines the morphological evolution of np-Au films.